Enhancing Growth, Yield, and Quality of Kohlrabi (Brassica oleracea var. caulorapa L.) with Biofertilizers: A Sustainable Approach for Reducing Chemical Fertilizer Dependency (South Asian Journal of Agriculture, 2025)
Chemical fertilizers significantly degrade soil health, prompting the exploration of biofertilizers as a viable alternative to reduce dependency and mitigate environmental impacts. This study aimed to evaluate the impact of a combination of bio-fertilizer and reduced chemical fertilizer application on the growth, yield, and quality of kohlrabi. The experiment employed a Randomized Complete Block Design (RCBD) with three replications, consisting of two factors: Factor A encompassed three kohlrabi varieties: V1 = Quick Star, V2 = Challenger, V3 = Rapid. Factor B involved different fertilizer management strategies: F0 = Recommended dose (160:120:60 kg/ha) of NPK (Control), F1 = 90% NPK + 2 kg/ha biofertilizer, F2 = 80% NPK + 4 kg/ha biofertilizer, and F3 = 70% NPK + 6 kg/ha biofertilizer. The experimental results demonstrated that both the choice of kohlrabi varieties and the application of various doses of bio-fertilizers significantly influenced the growth, yield, and quality of kohlrabi. The Challenger variety, when treated with a combination of 70% NPK and 6 kg/ha of biofertilizer, exhibited significant enhancements in various parameters compared to the untreated Challenger variety, including a 36.47% increase in fresh weight of knobs, a 26.7% boost in yield, a 13.3% rise in magnesium content, an 127% increase in potassium content, a remarkable 126.5% augmentation in manganese levels, and a 42.86% elevation in Vitamin C content. Hence, it is recommended that employing the combination treatment, consisting of 70% NPK along with 6 kg/ha of biofertilizer, during the cultivation of the Challenger variety could effectively stimulate plant growth and substantially improve both yield and quality of kohlrabi.South Asian J. Agric., Vol. 10, No.1-2, 2024: 24-35